2017
DOI: 10.1681/asn.2016080925
|View full text |Cite
|
Sign up to set email alerts
|

Histones and Neutrophil Extracellular Traps Enhance Tubular Necrosis and Remote Organ Injury in Ischemic AKI

Abstract: Severe AKI is often associated with multiorgan dysfunction, but the mechanisms of this remote tissue injury are unknown. We hypothesized that renal necroinflammation releases cytotoxic molecules that may cause remote organ damage. In hypoxia-induced tubular epithelial cell necrosis , histone secretion from ischemic tubular cells primed neutrophils to form neutrophil extracellular traps. These traps induced tubular epithelial cell death and stimulated neutrophil extracellular trap formation in fresh neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
246
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(257 citation statements)
references
References 45 publications
9
246
0
2
Order By: Relevance
“…recently investigated the role of circulating neutrophil extracellular traps and histones in remote organ injury after warm renal IRI 26. The authors investigated the systemic effects of AKI on remote organs and found that tubular necrosis and neutrophil extracellular trap formation promote kidney injury and remote organ damage due to the systemic release of proinflammatory cytokines and histones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recently investigated the role of circulating neutrophil extracellular traps and histones in remote organ injury after warm renal IRI 26. The authors investigated the systemic effects of AKI on remote organs and found that tubular necrosis and neutrophil extracellular trap formation promote kidney injury and remote organ damage due to the systemic release of proinflammatory cytokines and histones.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the histone-TLR-4 pathway prevented the hepatic pyroptosis caused by renal allograft IRI. In addition, VEGF was found to mitigate the histone-induced development of pyroptosis and subsequent hepatic inflammation and could serve as a therapeutic target within these pathophysiologic processes.It is interesting to note that Nakazawa et al recently investigated the role of circulating neutrophil extracellular traps and histones in remote organ injury after warm renal IRI 26. The authors investigated the systemic effects of AKI on remote organs and found that tubular necrosis and neutrophil extracellular trap formation promote kidney injury and remote organ damage due to the systemic release of proinflammatory cytokines and histones.…”
mentioning
confidence: 99%
“…Indeed, neutrophil necroptosis has also been reported using other triggers, for example, phorbol 12-myristate 13-acetate or crystalline microparticles using neutrophils isolated from Ripk3- ( and Mlkl)- deficient mice [19, 20]. It is likely that neutrophil necroptosis also contributes to other forms of AKI as neutrophils and neutrophil extracellular trap formation has been observed in AKI models involving either glomerular or tubular necrosis [21, 22]. Interestingly, Ripk3 -deficient mice did not display any phenotype in heterologous nephrotoxic nephritis [23], a model induced by an antiserum raised against glomerular antigens with similarities to anti-GBM disease and crescentic glomerulonephritis.…”
Section: Essential Proteins Of the Necroptosis Pathway Contributing Tmentioning
confidence: 99%
“…Fur thermore, NETs were detected in lungs only by immunofluorescence staining. NETs inhibition reduced lung injury also suggesting their involvement in lung remote injury after AKI [18].…”
Section: Introductionmentioning
confidence: 89%